Pengaruh Penerapan Demosi Dan Mutasi Terhadap Prestasi Kerja Karyawan Di Pt.Pltu Belang Belang Kabupaten Mamuju Sulawesi Barat - Mutiara; Agus Halim (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
This study aims to determine the effect of the implementation of demotion and mutation on employee job performance at PT. PLTU Belang-Belang, Mamuju Regency, West Sulawesi. Demotion and mutation are part of human resource management policies used to improve employee effectiveness and performance. This research uses a quantitative method with descriptive and verificative approaches. Data were collected through questionnaires distributed to employees of PT. PLTU Belang-Belang. The data analysis technique used is multiple linear regression analysis to examine the effect of independent variables on the dependent variable. The results show that demotion and mutation have a significant effect on employee job performance, both partially and simultaneously. Therefore, appropriate implementation of demotion and mutation policies can be an effective managerial strategy to improve employee job performance at PT. PLTU Belang-Belang. The data analysis technique used is multiple linear regression analysis to examine the effect of independent variables on the dependent variable. The results show that demotion and mutation have a significant effect on employee job performance, both partially and simultaneously. Therefore, appropriate implementation of demotion and mutation policies can be an effective managerial strategy to improve employee job performance at PT. PLTU Belang-Belang, Mamuju Regency.